Scapholunate Ligament Internal Brace 360-Degree Tenodesis (SLITT) Procedure - Kakar, Sanjeev; Greene, Ryan M. (Journal of Wrist Surgery, 2018)
Background Scapholunate (SL) joint instability is one of the most common injuries of the wrist and may result from a fall or high-energy mechanism on the outstretched hand. The purpose of this case report is to describe the outcome of a 360-degree tenodesis to the SL joint with an internal brace (SLITT) for the treatment of SL instability.Case Description A 42-year-old male patient underwent SL ligament reconstruction with the SLITT procedure 12 months after injury. Given the intrinsic stability of the reconstruction, Kirschner (K) wires were not used and an early range of motion protocol was initiated. Thirteen months after his reconstruction, he was back at work with maintenance of his carpal alignment. Discussion Since its initial description, a myriad of different surgical techniques for SL instability have been devised with varied success. These include capsular shrinkage, dorsal capsulodesis, reduction-association with a screw of the scapholunate joint (RASL), scapholunate axis method (SLAM), bone ligament bone grafts, and a variety of tendon reconstructions. Possible explanations for this varied outcome may be related to the use of soft tissue reconstructions for irreducible injuries and reconstruction of only the dorsal SL ligament. In addition, many of these techniques involve prolonged immobilization with the use of K-wires.Clinical Relevance The SLITT procedure reconstructs both the volar and dorsal SL ligament. Given the added stability afforded by intrinsic bracing, we feel that this reconstruction may permit earlier range of motion without the need for K-wire stabilization.
Keywords: scapholunate ligament; internal brace; 360-degree tenodesis; SLITT procedure